A new twist on sea silk: the peculiar protein ultrastructure of fan shell and pearl oyster byssus. Issue 27 (27th June 2018) - Pasche, Delphine; Horbelt, Nils; Marin, Frédéric; Motreuil, Sébastien; Macías-Sánchez, Elena; Falini, Giuseppe; Hwang, Dong Soo; Fratzl, Peter; Harrington, Matthew James
Abstract : Fan shell and pearl oyster byssus possess an unusual and previously unreported hierarchical structure consisting of globular proteins arranged in a helical superstructure. Abstract : Numerous mussel species produce byssal threads – tough proteinaceous fibers, which anchor mussels in aquatic habitats. Byssal threads from Mytilus species, which are comprised of modified collagen proteins – have become a veritable archetype for bio-inspired polymers due to their self-healing properties. However, threads from different species are comparatively much less understood. In particular, the byssus of Pinna nobilis comprises thousands of fine fibers utilized by humans for millennia to fashion lightweight golden fabrics known as sea silk. P. nobilis is very different from Mytilus from an ecological, morphological and evolutionary point of view and it stands to reason that the structure–function relationships of its byssus are distinct. Here, we performed compositional analysis, X-ray diffraction (XRD) and transmission electron microscopy (TEM) to investigate byssal threads of P. nobilis, as well as a closely related bivalve species ( Atrina pectinata ) and a distantly related one ( Pinctada fucata ). This comparative investigation revealed that all three threads share a similar molecular superstructure comprised of globular proteins organized helically into nanofibrils, which is completely distinct from the Mytilus thread ultrastructure, and more akin to the supramolecular organization of bacterial pili and F-actin. This unexpected discovery hints at a possible divergence in byssus evolution in Pinnidae mussels, perhaps related to selective pressures in their respective ecological niches.